727 Impact of Washington State COVID-19 Lockdown on Sleep. (3rd May 2021) - Peterson, Mary; Lundholm, Kirsie; Skeiky, Lillian; Van Dongen, Hans; Hansen, Devon
Abstract: Introduction: The COVID-19 pandemic caused a global disruption to daily routines. Studies using surveys and sleep-related applications on mobile devices suggest that the pandemic has contributed to increases in sleep disruption or onset of new sleep disturbances. We present results from a naturalistic at-home study in which objective sleep measurements were made using both a wrist actigraph (Actiwatch-2, Philips Respironics) and a non-contact monitoring device (SleepScore Max, SleepScore Labs), comparing sleep measurements obtained immediately before and after the start of the first mandatory COVID-19 stay-at-home order in Washington State. Methods: As part of a larger study, nine Washington State residents (ages 22–48, 5 female, 4 male; 6 insomniacs, 3 normal sleeper) were enrolled in a 10-week at-home sleep monitoring study, which involved 1 week of actigraphy, 8 weeks of non-contact monitoring (data available for 6 subjects), and 1 week of actigraphy. During the study, the Washington State governor issued a stay-at-home order, effective March 15, 2020. We compared sleep measurements obtained before this date (mean ± SD: 25.0 ± 15.0 nights) and after this date (25.2 ± 13.9 nights) using mixed-effects ANOVA. Results: Non-contact monitoring measurements indicated that after the start of the lockdown, participants woke up later by 63.2 ± 12.1 min (mean ± SE; F[1, 299]=27.40, p<0.001) without significant change in bedtime (F[1, 299]=0.29, p=0.59). Sleep latency lengthened by 4.0 ± 2.3 min (F[1, 295]=4.92, p=0.027), and there were increases in number of awakenings (F[1, 295]=6.22, p=0.013) and wake after sleep onset (F[1, 295]=12.58, p<0.001). Actigraphy data complemented these results, showing delayed sleep onset by 53.4 ± 15.1 min (F[1, 101]=12.46, p<0.001) and delayed final awakening by 104.3 ± 19.6 min (F[1, 101]=28.43, p<0.001), with longer sleep duration (F[1, 101]=6.06, p=0.016), increased number of awakenings (F[1, 101]=13.00, p<0.001), and a trend for increased intermittent wakefulness (F[1, 101]=3.88, p=0.052) post-lockdown. Conclusion: In this sample, we found evidence of increased sleep disruption following the first Washington State stay-at-home order related to COVID-19. Our findings are consistent with previous studies based on self-report data, which observed later wake times and decreases in sleep quality post-lockdown. Support (if any): NIH grant KL2TR002317. Non-contact monitoring devices provided by SleepScore Labs.